Observational study of inflammatory arthritis treatment by etanercept originator switched to an etanercept biosimilar - Felis-Giemza, Anna (Reumatologia, 2019)
OBJECTIVES: The aim of the study was to assess the safety and efficacy of switching an etanercept originator to an etanercept biosimilar in rheumatoid arthritis, juvenile idiopathic arthritis, psoriatic arthritis, and ankylosing spondylitis patients. MATERIAL AND METHODS: In 162 patients etanercept originator treatment had been replaced with the biosimilar (Group 1), and in six patients the biosimilar was initiated as the first biological agent (Group 2). The efficacy and safety of the treatment were monitored at 3–6 months. RESULTS: In the majority of patients in Group 1 (n = 138) the etanercept biosimilar was well tolerated, whereas in 24 patients a switch back to the originator was required. The loss of efficacy was confirmed in nine patients using clinical scoring system, and nine patients reported subjective loss of efficacy; 13 patients reported adverse events, most often headache (n = 3) and skin lesions (n = 3). In four patients injection site reactions were present. The adverse events (AE) and/or the loss of the biosimilar efficacy were more commonly observed in women, patients with rheumatoid arthritis (especially in those who did not receive methotrexate), and in patients with a previous history of any other biological treatment. In patients in Group 2 the therapy was effective and no adverse events were observed. CONCLUSIONS: The etanercept biosimilar seems to be effective and well-tolerated in the majority of patients. Nevertheless, in some cases, switching from the originator to the biosimilar was associated with AEs or loss of efficacy.